Land cover shifts strain resource nexus in southern Africa: evidence from Malawi - Makwinja, Yamikani Harry; O’Farrell, Patrick John; Kimengsi, Jude Ndzifon; Guenther, Edeltraud (Frontiers in Environmental Science, 2025)
Landscapes in southern Africa are subjected to significant dynamics related to Land Cover Change (LCC). While there is abundant research on Land Cover Trajectories (LCT), more comprehensive studies are still needed to determine the extent to which these changes reshape the Water-Energy-Food-Climate (WEFC) Nexus. We employed an explanatory sequential mixed-methods approach in Malawi using Case studies of Blantyre and Lilongwe districts to 1 explore trends in LCC from 1994 to 2024, and 2 analyse the effects of land cover trends on the WEFC Nexus. This approach involved conducting a quantitative analysis of Landsat images using ArcGIS software to determine the LCC and applying the Mann-Kendall statistical analysis test to identify trends in key land cover classes and associated resources. Qualitative data were gathered using ethnographic techniques, focus group discussions, key informant interviews, and expert interviews. These were analysed through deductive content analysis to provide complementary evidence. The analysis reveals 1 a dynamic land cover transformation characterised by a significant decline in forest cover, cropland expansion, and urbanisation. 2 LCC directions that weaken WEFC Nexus. Declining water productivity and increasing water stress are diminishing hydropower generation capacity and degrading ecosystem integrity, thereby threatening regional water and energy security. Concurrently, agricultural intensification has failed to ameliorate food insecurity within local communities. The study reveals significant inefficiencies in resource allocation and reflects profound underlying socioeconomic disparities. It offers valuable theoretical and policy implications for the Resource Nexus in southern Africa. It also highlights the significance of the WEFC Nexus in Malawi and serves as a pertinent example for other southern African nations facing similar challenges. It advocates for ongoing research and adaptive management strategies to address the interdependencies of these resources, supporting Nature-positive sustainable development and enhancing resilience against socio-environmental changes.